2010
DOI: 10.1186/1744-8069-6-80
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Functional Connectivity of the Periaqueductal Gray during Genuine and Sham Electroacupuncture Treatment

Abstract: BackgroundElectroacupuncture (EA) is currently one of the most popular acupuncture modalities. However, the continuous stimulation characteristic of EA treatment presents challenges to the use of conventional functional Magnetic Resonance Imaging (fMRI) approaches for the investigation of neural mechanisms mediating treatment response because of the requirement for brief and intermittent stimuli in event related or block designed task paradigms. A relatively new analysis method, functional connectivity fMRI (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 97 publications
(134 reference statements)
2
77
0
Order By: Relevance
“…This therapeutic method originated in China >2,000 years ago, and over time EA has been accepted as conventional medicine in clinical practice worldwide (1)(2)(3)(4). Statistical analyses of clinical results have indicated that the effects of EA on strokes are significant (5).…”
Section: Introductionmentioning
confidence: 99%
“…This therapeutic method originated in China >2,000 years ago, and over time EA has been accepted as conventional medicine in clinical practice worldwide (1)(2)(3)(4). Statistical analyses of clinical results have indicated that the effects of EA on strokes are significant (5).…”
Section: Introductionmentioning
confidence: 99%
“…As shown by Zyloney et al [35], EA leads to enhanced functional connectivity between precuneus, which shows the highest glucose consumption within the DMN, and periaqueductal gray [31]. The former is related to self-referential processing, the latter plays an important role in endogenous analgesia and is stimulated by AA [8,[36][37][38][39].…”
Section: Resultsmentioning
confidence: 95%
“…7,8 Zyloney et al found that continuous genuine electrical acupuncture stimulation can modify the coupling of spontaneous activity in brain regions that play a role in modulating pain perception. 9 Lumbar spinal stenosis is defined as narrowing of the intraspinal (central) canal, lateral recess, or neural foramen. Lateral recess and neural foraminal stenosis can cause nerve-root compression and a patient can present with radicular pain, weakness, or loss of sensation in the distribution of the affected spinal nerve.…”
Section: Introductionmentioning
confidence: 99%